Impact of Labor in Primary Cesarean Delivery on Subsequent Risk of Placenta Accreta - Kashani Ligumsky, Lior; Lopian, Miriam; Jeong, Anhyo; Desmond, Angela; Elmalech, Avshalom; Many, Ariel; Martinez, Guadalupe; Krakow, Deborah; Afshar, Yalda (American Journal of Perinatology, 2025)
This study aimed to evaluate whether a primary cesarean delivery (CD) performed during labor increases the risk of placenta accreta spectrum (PAS) disorders in a high-parity population with a low overall CD rate.This retrospective cohort study included singleton pregnancies with a confirmed International Federation of Gynecology and Obstetrics (FIGO) PAS diagnosis at a single tertiary center (2011–2022). Each PAS case was matched 1:1 to a control without PAS based on parity, number of previous CDs, and history of vaginal birth after cesarean. Multivariable logistic regression assessed the association between labored versus unlabored primary CD and PAS, adjusting for placenta previa, in vitro fertilization, prior postpartum hemorrhage, and prior dilation and curettage.Among 128,485 deliveries, 45 PAS cases (0.04%) were identified and matched to 45 controls. Median parity was 5.0; 34% had three or more prior CDs. Labored primary CD was associated with increased PAS risk (adjusted odds ratio: 6.3, 95% confidence interval [CI]: 1.7–23.3; p < 0.05). Placenta previa and prior postpartum hemorrhage were also independently associated with PAS. No significant differences in maternal or neonatal outcomes were observed between the labored and elective primary cesarean groups.Primary CD during labor increases PAS risk six-fold in subsequent pregnancies, warranting consideration in counseling and surgical decision-making.
Keywords: placenta accreta spectrum; labored cesarean delivery; elective cesarean delivery; risk factors